Medial temporal lobe activity at recognition increases with the duration of mnemonic delay during an object working memory task. - Picchioni, M; Matthiasson, P; Broome, M; Giampietro, V; Brammer, M; Mathes, B; Fletcher, P; Williams, S; McGuire, P (2007)
Object working memory (WM) engages a disseminated neural network, although the extent to which the length of time that data is held in WM influences regional activity within this network is unclear. We used functional magnetic resonance imaging to study a delayed matching to sample task in 14 healthy subjects, manipulating the duration of mnemonic delay. Across all lengths of delay, successful recognition was associated with the bilateral engagement of the inferior and middle frontal gyri and insula, the medial and inferior temporal, dorsal anterior cingulate and the posterior parietal cortices. As the length of time that data was held in WM increased, activation at recognition increased in the medial temporal, medial occipito-temporal, anterior cingulate and posterior parietal cortices. These results confirm the components of an object WM network required for successful recognition, and suggest that parts of this network, including the medial temporal cortex, are sensitive to the duration of mnemonic delay.